Does a Procurement Service Provider Generate Value for the Buyer Through Information About Supply Risks? - Yang, Zhibin (Ben); Babich, Volodymyr (Management Science, 2015)
We consider a supply chain with one buyer and two suppliers who are subject to disruptions and whose likelihoods of disruption are their private information. In such a setting, does the buyer benefit from engaging the services of a better-informed procurement service provider (PSP) compared to procuring directly from the suppliers? Intuition might suggest that hiring a PSP is always the right choice because the PSP’s knowledge of the supply base improves supplier selection and management. On the other hand, earlier studies prove that using a PSP purely for its superior knowledge about supply costs is always worse for a buyer than contracting with the suppliers directly. Our answer to this research question is more nuanced. Contrary to the findings of earlier studies, we find that the buyer may benefit from using a PSP. We identify, quantify, and explain all of the benefits and the costs of using a PSP, and describe conditions under which the benefits exceed the costs. The benefits of using a PSP are derived when one supplier is of high reliability and the other is of low reliability, from a reduction of informational costs due to implicit supplier collusion facilitated by the PSP and an improvement of supply availability. The costs of using a PSP are derived when both suppliers are of low reliability, from the loss of direct control over the supplier’s production actions, which leads to reduced supply availability and increased informational costs, and from the PSP facilitating implicit supplier collusion. Comparative statics analysis indicates that using the PSP is valuable only if the buyer diversifies with some supplier-type combinations but not others, and that hiring a PSP is not a solution to the problem of an unreliable supply base. This paper was accepted by Serguei Netessine, operations management.